2020
DOI: 10.1002/cncr.33140
|View full text |Cite
|
Sign up to set email alerts
|

Trends in screening breast magnetic resonance imaging use among US women, 2006 to 2016

Abstract: BACKGROUND: Supplemental breast cancer screening with breast magnetic resonance imaging (MRI) is recommended for women at high risk of breast cancer. To the authors' knowledge, recent national trends in breast MRI use are unknown. METHODS: The authors used claims data from a large national insurer to calculate screening breast MRI rates from 2006 to 2016 in a US cohort of 10 million women aged 20 to 64 years. Use was stratified by subgroups of women with a BRCA mutation, family history of breast cancer, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…In contrast, breast MRI rates were much higher in this cohort of survivors who underwent genetic testing (34.9% for P/LP and 14.3% for VUS in year 1) compared to 9% in the population level 3 . Our rates appear to be greater than results from a recent population level study that reported 0.12% rate of MRI in the overall population and 2.1% among BRCA mutation carriers 19 that likely indicates the influence of cancer care settings on receipt of guideline concordant medical management. In addition, our largely non‐Hispanic White, well‐insured study population likely have the resources to access routine surveillance that is known to be influenced by socioeconomic characteristics 20 .…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast, breast MRI rates were much higher in this cohort of survivors who underwent genetic testing (34.9% for P/LP and 14.3% for VUS in year 1) compared to 9% in the population level 3 . Our rates appear to be greater than results from a recent population level study that reported 0.12% rate of MRI in the overall population and 2.1% among BRCA mutation carriers 19 that likely indicates the influence of cancer care settings on receipt of guideline concordant medical management. In addition, our largely non‐Hispanic White, well‐insured study population likely have the resources to access routine surveillance that is known to be influenced by socioeconomic characteristics 20 .…”
Section: Discussioncontrasting
confidence: 87%
“…While our estimates of total additional spending are modest, they add up across the population. A claims-based study 28 showed about 0.18% of all US women aged 40 to 64 received screening MRI in 2016 (0.19% among women aged 40-49; 0.17% among women aged 50-64), with current rates likely to be higher. Extrapolating to 52.6 million women aged 40 to 64 based on 2020 US census data, this would entail about $53.4 million in additional total spending on mammary cascades and $4.0 million on extramammary cascades nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, bilateral breast MRI codes do not distinguish between screening and diagnostic indications, although we took several analytic steps to exclude diagnostic MRI consistent with prior literature. 28 , 29 In addition, potential cascade events necessarily include services commonly performed for various indications, so while we report these rates, our main conclusions focus on additional event rates in the breast MRI group compared with the mammography group. The falsification test offers further reassurance that the additional cascade events reported may plausibly be associated with the index event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Unfortunately, a lot of cancer patients were diagnosed in advanced stages or metastatic stage, missing the best time for treatment. At present, despite the abundant clinical diagnostic methods, including magnetic resonance imaging (MRI), positron emission tomography-computed tomography (PET-CT), and mammography combine with histopathology or cytology, [3][4][5][6][7] these methods suffer from the high cost, complicated procedure, invasiveness, and subjective visual identification based on experience of pathologist. Thus, over treatment or missed diagnosis possibly exists due to the false-positive or false-negative caused by above methods, leading to miserable outcomes to the patients.…”
Section: Introductionmentioning
confidence: 99%